Edutainment-Based Disaster Education Strategies from a Community Empowerment Perspective to Enhance Early Childhood Disaster Literacy - Eva Tatia Fazriani; Agus Sriyanto (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Disaster literacy should be introduced during early childhood to strengthen preparedness and reduce future disaster risks; however, conventional instructional approaches often fail to provide meaningful learning experiences for young children. This study aimed to examine the implementation of edutainment-based disaster education in enhancing disaster literacy among early childhood learners from a community empowerment perspective. A qualitative case study was conducted at the Banyumas Regional Disaster Management Agency (BPBD), Indonesia, involving two disaster education facilitators and fifteen early childhood learners selected through purposive sampling. Data were collected through semi-structured interviews, participatory observations, and documentation, and analyzed using thematic analysis involving open, axial, and selective coding. The findings indicate that integrating educational games, disaster simulations, songs, and visual media promotes active participation, strengthens children's understanding of disaster risks, and improves practical preparedness skills through experiential learning. The study further reveals that facilitators play a crucial role in creating participatory learning environments that support community awareness and collective responsibility for disaster preparedness. Nevertheless, limited instructional time and the diverse developmental characteristics of young learners remain important challenges for program implementation. This study contributes to disaster education literature by conceptualizing edutainment as an integrated pedagogical approach that links experiential learning with community empowerment, while providing practical guidance for developing child-centered and sustainable disaster education programs in disaster-prone communities.